Mengenali Masalah-masalah Hukum E-commerce - Rusli, Hardijan (LAW REVIEW, 2001)
Companies have ventured onto the Information Superhighway in increasing numbers to  "reduce distribution and marketing costs eliminate the middleman increase efficiency,  promote impulse transactions and streamline distribution to far-flung locales" as well as to  "connect directly with consumers at home streamline operations and internal transactions,  and increase business -to- business sales. The value of US based-commerce transactions was estimated to be $ 43 billion in 1998, and projected to grow to $ 1.3 trillion by 2003, over nine percent of total US business sales. More importantly, electronic commerce ("e-commerce ") stands on the threshold of broad global acceptance. According to projections bv one research firm, worldwide e-commerce sales will reach as high as $ 3.2 trillion in 2003, reprensenting nearly five percent of all global sales. Likewise, governments around the world have enthusiastically embraced e-commerce as a positive development that should be encouraged. For example, numerous governments have announced that fostering e-commerce is a major public policy objective. Indeed,  governments themselves have benefited from the e-commerce revolution by launching their own Web sites to better communicate with and serve constituents while reducing transaction costs. State upon state, and country upon country, have noted this movement online and responded by proposing, and in many cases enacting, e-commerce legislation and regulations on a wide variety of topics: taxation of e-commerce transactions, jurisdiction over online transactions, data protection and data privacy, confidentiality of e-commerce transaction (including export controls of encryption products), unsolicited commercial e-mail (spam), information security, and the enforceability of e-commerce transactions. (Thomas J. Smedinghoff, and Ruth Hill Bro.; Moving With Change: Electronic Signature, Legislation As A Vehicle For Advancing E-Commerce).How is Indonesia? Is Indonesia ready to have ONLINE LAW? Like Robert F Kennedy said that "unless we moved with change we would become its victims ".Indonesia has to have e-commerce transaction act because it is a positive development so there is no reason for not setting up the essential law. This article is about introducing what legal issues in e-commerce transactions.